2022
DOI: 10.1088/1748-9326/ac810f
|View full text |Cite
|
Sign up to set email alerts
|

On farmers’ perceptions of climate change and its nexus with climate data and adaptive capacity. A comprehensive review

Abstract: Farmers’ perception of climate change is crucial in adaptation intention and process. However, farmers’ perceptions may not be timely, accurate and systematically consistent with the direction and significance of observational records. Although some research compared farmers’ perceptions and climate data, little attention has been paid to comprehensibly analyse both data sources discrepancies based on empirical studies results. By combining bibliometrics and a systematic review approach, we identify which appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 192 publications
0
11
0
Order By: Relevance
“…However, more than 90 per cent of the sample, especially when it came to the average summer temperature, perceived the temperature to be rising, according to Ricart et al (2022). In terms of increased frequency and severity, farmers ranked drought risk higher than flood risk, with significant internal consistency across the samples (90% vs. 70%, respectively).…”
Section: B People's Perception On Climate Change In Global Contextmentioning
confidence: 97%
“…However, more than 90 per cent of the sample, especially when it came to the average summer temperature, perceived the temperature to be rising, according to Ricart et al (2022). In terms of increased frequency and severity, farmers ranked drought risk higher than flood risk, with significant internal consistency across the samples (90% vs. 70%, respectively).…”
Section: B People's Perception On Climate Change In Global Contextmentioning
confidence: 97%
“…Some researchers have evaluated the precision of farmers’ perceptions of climate change. For example, Belay Bedeke and Tebeje (2022) and Ricart et al (2022) examined the connection between farmers' perceptions of long-term variations in temperature and precipitation and the climatic patterns noted by the adjacent meteorological stations. This study observed that the farmers’ perceptions conformed with the definite national climate data presented in Figure 5.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…The literature review conducted by Ricart et al. (2022) reported that research on perceptions of climate change impacts was generally dominated by southern and eastern African countries (Ethiopia, Kenya, and Tanzania) and South Asia (Bangladesh, Nepal) with few cases from the northern, central, and western regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, adaptation to the effects of climate change is required in order to reduce the vulnerability of their livelihood systems. Farmers implemented a wide range of adaptation measures in response to climate change conditions, such as non-farm activities ( Ali et al., 2021 ), improved seed variety ( Dendir and Simane, 2021 ), and crop diversification ( Ricart et al., 2022 ). Previous researches have found that farmers who have a good understanding and perception of climate change are more likely to choose the appropriate adaptation strategy ( Fahad et al., 2020 ; Ojo and Baiyegunhi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%